WAYS OF INCREASING THE FINANCIAL STABILITY OF OIL REFINING INDUSTRY IN MODERN CONDITIONS - V. Ashikhin (Вестник университета, 2017)
The article defines the concept of financial stability of an enterprise as an indicator of economic stability in modern conditions. The main financial and industrial indicators of Russian oil refining industry enterprises are considered. The ways of increasing financial stability of enterprises are suggested.